The role of NPC1L1 in cancer - Zhang, Renshuai; Zeng, Jun; Liu, Wenjing; Meng, Jingsen; Wang, Chao; Shi, Lingyu; Yang, Shanbo; Chang, Jing; Xing, Dongming (Frontiers in Pharmacology, 2022)
Lipid metabolism appears to play significant roles in the development of cancer. Numerous studies have shown that the evolution of malignancies, including breast, prostate, and colorectal cancers, involves cholesterol in a profound manner. A crucial part in the intestinal absorption of cholesterol is played by Niemann–Pick C1-like 1 (NPC1L1), a cholesterol transporter protein that is widely expressed in the small intestine and liver. The importance of NPC1L1 in tumor prognosis has been demonstrated in investigations in the interim. NPC1L1 also has the potential to develop into a new therapeutic target and a cancer marker. There is, however, no comprehensive review that summarizes NPC1L1’s function in cancer. To this end, we outlined NPC1L1’s functions in carcinogenesis and treatment, along with resources that can be used to further comprehend the connection between NPC1L1 and tumors.